Design and Build an Information System for Management of Incoming and Outgoing Mail Archives Based on a Website at the Bandung Subdivre Logistics Affairs Agency (BULOG) - Muhamad Fahmi Nugraha; Yunita Sulistiani; Ajeng Rahayu (International Journal of Research in Community Services, 2023)
The design of information for managing incoming and outgoing mail archives is made to solve problems that occur in the Agency for Logistics Affairs (BULOG) Subdivre Bandung in terms of managing mail archives, namely manual mail archives management, causing data loss. This research was made based on a method approach in collecting the information data needed in order to make a description of the situation, event. While the system development method used is the RUP (Rational Unified Process) model with OOAD (Object Oriented Analysis and Design) where the development tool is in the form of UML (Unified Modeling Language). The purpose of the research and from the interviews that have been carried out, the solution to overcome the above problems is to create a website-based mail archive system that can be accessed anytime and anywhere.